Regulating the Quasi-Military Use of Large Low-Earth Orbit Satellite Constellations under International Space Law (International relations and international law Journal, 2026)
This article examines the regulatory dilemma created by the quasi-military use of large low-Earth orbit (LEO) satellite constellations. It argues that the five cornerstone instruments of international space law - the Outer Space Treaty, the Moon Agreement, the Liability Convention, the Registration Convention, and the Rescue Agreement - still provide the basic legal framework for space activities, but they do not fully address the legal consequences of modern commercial constellations that may support military operations. The central problem is not only the direct militarization of outer space, but also the growing use of ostensibly civilian space infrastructure for communication, imaging, targeting support, and other functions connected to terrestrial conflict. The article identifies several regulatory gaps: the abstract character of the principle of peaceful use, the narrow prohibition on weapons of mass destruction, the uncertainty surrounding dual-use objects, the weakness of consultation procedures, the absence of compulsory adjudication, the difficulty of attributing responsibility for private operators, and the limited scope of compensation for non-physical or indirect damage. It further shows that registration practice and recent national space-security policies have not removed these gaps. On this basis, the article concludes that large LEO constellations expose a structural mismatch between treaty rules drafted in the Cold War period and contemporary space activities shaped by private companies, military demand, and dual-use technologies.Keywords: large low-Earth orbit constellations, quasi-military use, international space law, peaceful use of outer space, legal regulation